Reproductive and Productive Performance of Surti Buffaloes as Influenced by Different Protein Levels around Parturition - Sarvaiya, Nitesh P; Parmar, Abhishek B; Parmar, Ajay P; Patel, Dilip C (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The transition period is the most stressful in the annual cycle of dairy animals, particularly buffaloes, as feed intake is reduced, while the demand for support of fetal growth and galactopoietic functions are increased. This experiment was carried out on the 30 advanced pregnant Surti buffaloes in two phases (15 each) from 210 days of gestation till 90 days postpartum to evaluate the effect of varying level of protein feeding on their productive and reproductive performance. The animals were randomly divided into three equal groups each of 10 (5+5) animals. Control group (n=10) was fed concentrate mixture to meet the nutrient requirement as per ICAR (2013) standards. Whereas, treatment group 1 and 2 consisted of 15% and 25% more CP % of requirements, respectively, over Control group. Results revealed that at parturition buffaloes in all the three groups experienced reduction in body weight of around 35 kg due to expulsion of fetus, placenta and lochia. However, in treated groups of buffaloes within three months postpartum rise in body weight was observed. Moreover, no significant difference was observed in placental expulsion time or weight of placenta or time taken for uterine involution and onset of first postpartum estrus. milk production of first three months and peak yield per day were significantly higher in the buffaloes fed with 25% more CP. Moreover, fat per cent, 6 % FCM whole milk yield and milk yield per day were also significantly (p<0.05) higher in buffaloes fed with 25% more CP. It was concluded that 25% more CP supplementation have increased milk yield and improved milk composition without any adverse effect on reproductive health status of buffaloes.